2018
DOI: 10.1139/cjfas-2017-0335
|View full text |Cite
|
Sign up to set email alerts
|

Estimating observer error and steelhead redd abundance using a modified Gaussian area-under-the-curve framework

Abstract: This study examined how a suite of habitat and environmental variables relate to the ability of a stream surveyor to identify (observer efficiency) and distinguish (observer accuracy) steelhead (Oncorhynchus mykiss) redds from other stream features. Two existing spawning survey protocols that included one or two redd observers were used to develop models to estimate redd observer error. In most cases, steelhead redd abundances using raw redd counts were underestimated. Mean annual rates of observer efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Covariates that were important in influencing spring Chinook error rates were also important for steelhead redd survey error rates (Murdoch et al, ). However, important differences in these studies are worth noting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Covariates that were important in influencing spring Chinook error rates were also important for steelhead redd survey error rates (Murdoch et al, ). However, important differences in these studies are worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the commission error rate or the proportion of features identified that were not spring Chinook Salmon redds (e.g., hydraulic scour and depositional areas, test redds, or redds of other species) as: Ci=trueEiFi, where C i is the error rate of commission, E i is the number of features erroneously identified as redds, and F i is the total number of redd‐like features found by the naïve redd observer i . This corresponds to one minus the accuracy rate described in (Murdoch et al, ). We defined the omission error rate or the proportion of actual redds missed by naïve surveyors as: Oi=trueMiVitaliccen, where O i is the omission rate, M i is the number of redds found by the census surveyors but missed by the naïve surveyor i , and V cen is the number of visible redds identified by the census surveyors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations